2007
DOI: 10.4049/jimmunol.178.5.2714
|View full text |Cite
|
Sign up to set email alerts
|

PD-1:PD-L1 Interactions Contribute to the Functional Suppression of Virus-Specific CD8+ T Lymphocytes in the Liver

Abstract: Mechanisms contributing to the development of chronic viral infections, including chronic hepatitis B virus (HBV) infections, are not well understood. We have shown recently that production of IFN-γ, an important antiviral cytokine, by HBV-specific CTLs is rapidly induced when they enter the liver of HBV transgenic mice, and then rapidly suppressed, despite the continued presence of Ag. Suppression of IFN-γ production by the CTLs coincides with the up-regulation of programmed cell death (PD)-1, a cell surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
172
0
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(190 citation statements)
references
References 47 publications
11
172
0
4
Order By: Relevance
“…The expression levels of PD-1 were found to be high on the virus-specific T cells during persistent chronic HIV and HCV infection (19,20). In the present study, we observed a significant elevation in the expression of PD-1 on either CD4 or CD8 T cells in the pre-treatment group compared to the normal group, which was similar to the observations of recent studies on HBV (21)(22)(23)(24). Notably, the levels of PD-1 on CD8 T cells in the post-treatment group were significantly decreased compared to those in the pre-treatment group.…”
Section: A B C Discussionsupporting
confidence: 81%
“…The expression levels of PD-1 were found to be high on the virus-specific T cells during persistent chronic HIV and HCV infection (19,20). In the present study, we observed a significant elevation in the expression of PD-1 on either CD4 or CD8 T cells in the pre-treatment group compared to the normal group, which was similar to the observations of recent studies on HBV (21)(22)(23)(24). Notably, the levels of PD-1 on CD8 T cells in the post-treatment group were significantly decreased compared to those in the pre-treatment group.…”
Section: A B C Discussionsupporting
confidence: 81%
“…The role of PD-1/B7-H1 as a mechanism for liver tolerance has been well established. Indeed, PD-1 expression by T cells has been shown to inhibit intrahepatic antiviral immune responses at the effector phase (20,21,38). The initial induction of PD-1 by CD8 ϩ T cells in both core(ϩ) and core(Ϫ) mice at the early stage of viral infection provides further evidence that PD-1 plays an important role in controlling intrahepatic T cell responses.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, B7-H1 plays a pivotal role in the accumulation and deletion of intrahepatic CD8 ϩ T cells (19). Importantly, the PD-1/ B7-H1 inhibitory pathway has been shown to be involved in the regulation of intrahepatic T cell responses (20,21). However, it is currently not known how the PD-1/B7-H1 pathway contributes to the HCV core-mediated immune dysregulation leading to viral persistence.…”
mentioning
confidence: 99%
“…119 However, there are also data suggesting that most intrahepatic CD8 ϩ T cells are toleragenic and express PD-1. 120 One of the evasion mechanisms used by HCV to escape immune responses, especially CD8 responses, is the development of viral escape mutants. 121 Finally, a significant correlation has been demonstrated between the number of lobular CD8 ϩ T cells and ALT levels, suggesting a prominent role for T cell-mediated cytotoxicity in the genesis of hepatocellular damage.…”
Section: Role Of Cd8 T Cellsmentioning
confidence: 99%